Preparation method of high-light-fastness color-changing type softwood-based board

By adding multi-site polymers and nanotitanium dioxide to the adhesive of the cork substrate, a light-resistant color change layer is formed, which solves the problem of easy color change of the cork substrate and improves the high light-resistant color change performance.

CN119795315AActive Publication Date: 2025-04-11MASS NEW MATERIALS TECHNOLOGY RESEARCH (CHANGZHOU) CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510069227.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-11
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Due to its chemical composition, cork substrates are susceptible to light discoloration and cause light discoloration, which limits their application range.

Method used

By adding multi-site polymer bonding/organic antioxidant-nano-titanium dioxide intercalated hydrotalcite organic-inorganic composite modifier to the elastic polyurethane adhesive, a light-resistant color change layer is formed, and the light-resistant color change performance of the cork substrate is improved.

Benefits of technology

It has achieved improved light-resistant and color-changing performance of cork substrates, simple operation, no change in color of cork substrates itself, and no impact on subsequent processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119795315A_ABST
    Figure CN119795315A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of processing of artificial boards, in particular to a preparation method of a high-light-resistance color-changing type cork-based board, which comprises the following preparation steps: S1, preparing a modifier; s2, preparing a modified adhesive; and S3, preparing the plate. By adding the photochromic modifier into the adhesive for the softwood-based board, the photochromic property of the softwood-based board can be greatly improved, and the operation is simple. And the added modifier does not change the color of the cork-based board and has no influence on subsequent processing such as dyeing and coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of processing of artificial boards, in particular to a method for preparing a highly light-resistant and discoloration-resistant cork-based board. Background Art

[0002] Cork is the outer bark of cork trees, which is soft and elastic. The most common use of cork is as cork stoppers, but due to its natural texture, feel, touch and environmental performance, it has also had good development prospects in the decoration industry in recent years. The remaining cork particles can be mixed with adhesives and molded into various boards, that is, cork-based boards can be used for floors, wall panels, protective panels, interior panels, etc., which is an effective way to increase its added value. However, the chemical composition of cork is mainly suberin, lignin, cellulose, hemicellulose, extracts and ash, among which suberin and lignin account for a higher proportion, which makes cork-based boards more susceptible to light discoloration than natural wood boards, thereby limiting the application of cork-based boards. Therefore, it is of great significance to develop highly light-resistant cork-based boards.

[0003] One way to improve the light-discoloration resistance of cork-based boards is to give them new color patterns by printing high-color fastness dyes on the surface, and apply a weather-resistant coating to improve their light-discoloration resistance. For example, Lu Zhihua et al. (China Wood-Based Panels, 2021) used a flatbed UV inkjet printer to print cork floors, and their actual light-fastness reached level 4 or above. There is also a method of applying a weather-resistant decorative layer on the surface of cork-based boards, such as Song Zhuwan (CN201611061951.5) applied a pretreated fiber layer on the surface of the cork layer to improve the light-discoloration resistance of the cork base layer. Guo Anru et al. (CN201810425192.9) formed a flexible styrene-butadiene-styrene block copolymer / epoxy resin hydrophobic layer on the surface of the cork composite material, so that the cork composite board does not change color, peel off, etc. in a humid environment. However, these methods will change the color of the cork material itself to a certain extent and cannot be used to make color-changing cork-based boards. Therefore, it is very necessary to prepare a highly light-resistant cork-based board while retaining the color of the cork itself. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a highly light-resistant cork-based board material, using a multi-site polymer adhesive / organic antioxidant-nano-titanium dioxide intercalated hydrotalcite organic-inorganic composite modifier, adding it to an elastic polyurethane adhesive, compounding it with cork particles, and wrapping the adhesive on the surface of the cork particles to form a light-resistant discoloration layer during bonding, thereby improving the light-resistant discoloration performance of the cork-based board material. The preparation method is simple, and only the modifier needs to be added to the adhesive to achieve the improvement of the overall light-resistant discoloration performance of the board material.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a highly light-resistant and discoloration-resistant cork-based board material comprises the following steps:

[0007] S1. Preparation of the modifier: 1-3 parts of a multi-site polymer, 0.05-1 parts of an organic antioxidant, and 0.03-0.08 parts of nano-titanium dioxide are mixed at room temperature, and then 1-2 parts of hydrotalcite powder are added for grinding, and centrifuged by a centrifuge, and washed with anhydrous ethanol to obtain a modifier;

[0008] S2. Preparation of modified adhesive: The modifier was added to 12-18 parts of elastic polyurethane adhesive and stirred evenly, and 0.05-0.1 parts of acetone was added to reduce the viscosity of the reaction system to obtain a modified adhesive;

[0009] S3. Preparation of board: 80-85 parts of cork particles and the modified adhesive obtained in step S2 are mixed evenly in a glue mixer, and then added into a mold, and pressed at room temperature for 24-48 hours. The pressure is controlled at 0.1-0.2MPa, and the pressure is maintained and heated to 120-140℃ for hot pressing for 5-10 minutes to obtain a highly light-resistant and color-changing cork-based board.

[0010] Preferably, the preparation of the multi-site polymer comprises the following steps:

[0011] S11. The polyethyleneimine having a molecular weight of 1000-10000 is dissolved in water to prepare a polyethyleneimine aqueous solution having a mass fraction of 50-60%;

[0012] S12. Add 10-15% of the mass of polybasic organic acid in the polyethyleneimine aqueous solution, and stir at 40-60° C. for 8-10 minutes to obtain a multi-site polymer.

[0013] Preferably, the stirring speed in steps S2 and S3 is 300-500 r / min, and the time is 10-15 min.

[0014] Preferably, the polybasic organic acid is one or more of trihydroxymethylpropane acid, tricarboxymethane acid, and 3-carboxy-3-hydroxyglutaric acid.

[0015] Preferably, the elastic polyurethane adhesive is a two-component polyurethane adhesive consisting of component A and component B, wherein component A is a main agent, which is a polyurethane prepolymer containing terminal isocyanate groups, accounting for 65-70% of the mass fraction of the elastic polyurethane adhesive, and component B is a curing agent, which is a polyester polyol, accounting for 30-35% of the mass fraction of the elastic polyurethane adhesive.

[0016] Preferably, the organic antioxidant is a hindered phenol antioxidant.

[0017] Preferably, the average particle size of nano titanium dioxide is 20-100 nm.

[0018] Preferably, the preparation of hydrotalcite comprises the following steps:

[0019] S21. 1-2 parts by mass fraction of 60-70% aluminum nitrate aqueous solution, 2-4 parts by mass fraction of 60-70% magnesium nitrate aqueous solution, 1-2 parts by mass fraction of 60-70% sodium hydroxide aqueous solution, 3-7 parts by mass fraction of 60-70% sodium carbonate aqueous solution are slowly added dropwise together to obtain a slurry;

[0020] S22. The obtained slurry was immediately transferred to an autoclave, aged at 90-100°C, centrifuged, washed several times with anhydrous ethanol, dried at 80-100°C, and crushed through an 80-mesh sieve to obtain hydrotalcite.

[0021] Preferably, the cork particles have a particle size of 10-100 meshes.

[0022] Preferably, in step S1, the grinding process is carried out in a planetary ball mill at a rotation speed of 800-1000 r / min for 1-2 h.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention uses a multi-site polymer as a reactive center point to chemically graft an antioxidant and nano-titanium dioxide to form an organic-inorganic hybrid system, synergistically improves light discoloration resistance, and intercalates the active ingredients into the interior of the hydrotalcite through the interlayer adsorption performance of the hydrotalcite, thereby preparing a solid modifier that is easy to preserve.

[0025] 2. The modifier prepared by the present invention has good compatibility with the polyurethane adhesive, has no precipitation, agglomeration, demulsification and the like, does not change the curing characteristics of the adhesive, and has no effect on the bonding strength of the board.

[0026] 3. The present invention can significantly improve the light discoloration resistance of the cork-based board by adding a light discoloration resistance modifier to the adhesive for the cork-based board, and the operation is simple. The added modifier does not change the color of the cork-based board itself and has no effect on subsequent processing, such as dyeing, painting, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a process flow chart of the preparation of the highly light-resistant and color-changing cork-based board of the present invention;

[0028] Figure 2 The present invention is a process flow chart for preparing the multi-site polymer;

[0029] Figure 3 The present invention is a process flow chart of the preparation of hydrotalcite. DETAILED DESCRIPTION

[0030] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] See also Figure 1-3 , the present invention provides a technical solution:

[0032] Example 1

[0033] A highly light-resistant and discoloration-resistant cork-based board material:

[0034] S101. Preparation of the modifier: 20 g of a multi-site polymer, 0.8 g of a hindered phenol antioxidant 1010, and 0.3 g of nano-titanium dioxide were mixed at room temperature, and then 20 g of hydrotalcite powder was added, and the mixture was ground in a planetary ball mill at a speed of 800 r / min for 1 h, and centrifuged by a centrifuge, and washed with anhydrous ethanol to obtain a modifier;

[0035] S102. Preparation of modified adhesive: The modifier was added to 120 g of elastic polyurethane adhesive and stirred at a speed of 300 r / min for 10 min, and 0.5 g of acetone was added to reduce the viscosity of the reaction system to obtain a modified adhesive;

[0036] S103. Preparation of the board: 800 g of cork particles and the modified adhesive obtained in step S102 were stirred in a glue mixer at a speed of 300 r / min for 10 min, then added to a mold, pressed at room temperature for 24 h, the pressure was controlled at 0.1 MPa, and then heated to 120 ° C for 5 min to obtain a highly light-resistant cork-based board;

[0037] In this embodiment, the preparation of the multi-site polymer includes the following steps:

[0038] S10111. Dissolving polyethyleneimine in water to prepare a polyethyleneimine aqueous solution having a mass fraction of 50%;

[0039] S10112. Then add 10% trihydroxymethyl propane acid in a polyethyleneimine aqueous solution and stir at 40 ° C for 10 min to obtain a multi-site polymer;

[0040] The preparation of hydrotalcite comprises the following steps:

[0041] S10121. 1 part of 60% by mass aluminum nitrate aqueous solution, 2 parts of 60% by mass magnesium nitrate aqueous solution, 1 part of 60% by mass sodium hydroxide aqueous solution, and 3 parts of 60% by mass sodium carbonate aqueous solution are slowly added dropwise together to obtain a slurry;

[0042] S10122. The obtained slurry was immediately transferred to an autoclave, aged at 90°C, centrifuged, washed several times with anhydrous ethanol, dried at 80°C, and crushed through an 80-mesh sieve to obtain hydrotalcite.

[0043] Example 2

[0044] A highly light-resistant and discoloration-resistant cork-based board material:

[0045] S201. Preparation of modifier: 10 g of multi-site polymer, 10 g of hindered phenol antioxidant 1076, and 0.5 g of nano-titanium dioxide were mixed at room temperature, and then 10 g of hydrotalcite powder was added, and the mixture was ground in a planetary ball mill at a speed of 1000 r / min for 2 h, and centrifuged by a centrifuge, and washed with anhydrous ethanol to obtain a modifier;

[0046] S202. Preparation of modified adhesive: The modifier was added to 150 g of elastic polyurethane adhesive and stirred at a speed of 500 r / min for 15 min, and 1 g of acetone was added to reduce the viscosity of the reaction system to obtain a modified adhesive;

[0047] S203. Preparation of the board: 830 g of cork particles and the modified adhesive obtained in step S202 were stirred in a glue mixer at a speed of 500 r / min for 15 min, then added to a mold, pressed at room temperature for 48 h, the pressure was controlled at 0.2 MPa, and then heated to 140 ° C and hot pressed for 10 min to obtain a highly light-resistant cork-based board;

[0048] In this embodiment, the preparation of the multi-site polymer includes the following steps:

[0049] S20111. Dissolving polyethyleneimine in water to prepare a polyethyleneimine aqueous solution having a mass fraction of 60%;

[0050] S20112. Then add 15% tricarboxymethane acid in a polyethyleneimine aqueous solution and stir at 60 ° C for 10 min to obtain a multi-site polymer;

[0051] The preparation of hydrotalcite comprises the following steps:

[0052] S20121. 2 parts of 70% by mass aluminum nitrate aqueous solution, 4 parts of 70% by mass magnesium nitrate aqueous solution, 2 parts of 70% by mass sodium hydroxide aqueous solution, and 7 parts of 70% by mass sodium carbonate aqueous solution are slowly added dropwise together to obtain a slurry;

[0053] S20122. The obtained slurry was immediately transferred to an autoclave, aged at 100°C, centrifuged, washed several times with anhydrous ethanol, dried at 100°C and crushed through an 80-mesh sieve to obtain hydrotalcite.

[0054] Example 3

[0055] A highly light-resistant and discoloration-resistant cork-based board material:

[0056] S301. Preparation of modifier: 30 g of multi-site polymer, 0.8 g of hindered phenol antioxidant 1010, and 0.8 g of nano-titanium dioxide were mixed at room temperature, and then 20 g of hydrotalcite powder was added, and ground at a speed of 900 r / min in a planetary ball mill for 1.5 h, and centrifuged by a centrifuge, and washed with anhydrous ethanol to obtain a modifier;

[0057] S302. Preparation of modified adhesive: The modifier was added to 180 g of elastic polyurethane adhesive and stirred at a speed of 400 r / min for 12 min, and 0.5 g of acetone was added to reduce the viscosity of the reaction system to obtain a modified adhesive;

[0058] S303. Preparation of the board: 800 g of cork particles and the modified adhesive obtained in step S302 were stirred in a glue mixer at a speed of 400 r / min for 13 min, then added to a mold, pressed at room temperature for 36 h, the pressure was controlled at 0.1 MPa, and then heated to 130 ° C and hot pressed for 7 min to obtain a highly light-resistant cork-based board;

[0059] In this embodiment, the preparation of the multi-site polymer includes the following steps:

[0060] S30111. Dissolving polyethyleneimine in water to prepare a polyethyleneimine aqueous solution having a mass fraction of 55%;

[0061] S30112. Then add 12% 3-carboxy-3-hydroxyglutaric acid in a polyethyleneimine aqueous solution, and stir at 50 ° C for 9 minutes to obtain a multi-site polymer;

[0062] The preparation of hydrotalcite comprises the following steps:

[0063] S30121. 2 parts by mass of 65% aluminum nitrate aqueous solution, 3 parts by mass of 65% magnesium nitrate aqueous solution, 1 part by mass of 65% sodium hydroxide aqueous solution, and 5 parts by mass of 65% sodium carbonate aqueous solution are slowly added dropwise together to obtain a slurry;

[0064] S30122. The obtained slurry was immediately transferred to an autoclave, aged at 95°C, centrifuged, washed several times with anhydrous ethanol, dried at 90°C, and crushed through an 80-mesh sieve to obtain hydrotalcite.

[0065] Comparative Example 1

[0066] Comparative Example 1 is different from Example 1 in that multi-site polymer, organic antioxidant, nano titanium dioxide and hydrotalcite are not added in this comparative example.

[0067] Comparative Example 2

[0068] Comparative Example 2 is different from Example 1 in that the multi-site polymer, organic antioxidant and nano titanium dioxide are not added in this comparative example.

[0069] Comparative Example 3

[0070] Comparative Example 3 is different from Example 1 in that no multi-site polymer is added in this comparative example.

[0071] Comparative Example 4

[0072] Comparative Example 4 is different from Example 1 in that no organic antioxidant is added in this comparative example.

[0073] Comparative Example 5

[0074] Comparative Example 5 is different from Example 1 in that nano titanium dioxide is not added in this comparative example.

[0075] Performance Testing:

[0076] Compared with Example 1, Comparative Example 1 does not add multi-site polymer, organic antioxidant, nano titanium dioxide and hydrotalcite, Comparative Example 2 does not add multi-site polymer, organic antioxidant and nano titanium dioxide, Comparative Example 3 does not add multi-site polymer, Comparative Example 4 does not add organic antioxidant, and Comparative Example 5 does not add nano titanium dioxide. The modified adhesives obtained in Examples 1-3 and Comparative Examples 1-5 were tested for appearance, solid content and viscosity, and the obtained cork-based board was tested for water absorption thickness expansion rate, tensile strength and light fastness according to the national standard GB / T 17657-2022. The results are shown in Tables 1 and 2 below:

[0077] Table 1 Modified adhesive properties

[0078]

[0079] Table 2 Comparison of cork-based board properties

[0080]

[0081] From the results in Table 1, it can be seen that the appearance, solid content and viscosity of Examples 1-3 after adding the modifier are basically unchanged compared with the pure adhesive Example 1, but Comparative Examples 2 and 3 without adding the multi-point polymer both showed sedimentation, demulsification and other phenomena and could not be used. The performance of Comparative Examples 4 and 5 is basically the same as that of the pure adhesive Example 1.

[0082] From the results in Table 2, it can be seen that compared with the pure adhesive comparative example 1, the 24h water absorption thickness expansion rate, tensile strength and other properties of Examples 1-3 are not affected, and the light fastness reaches level 5, while the comparative example 1 is only grayscale level 2. Since the organic-inorganic synergistic light fastness discoloration characteristics are not formed in comparative examples 4 and 5, the light fastness is only slightly improved to level 3. This shows that the prepared modifier has good compatibility with the polyurethane adhesive, without precipitation, agglomeration, demulsification and other phenomena, does not change the curing characteristics of the adhesive, and has no effect on the bonding strength of the board.

[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a highly light-resistant and color-changing cork-based board, characterized in that: The method comprises the following preparation steps: S1. Preparation of the modifier: 1-3 parts of a multi-site polymer, 0.05-1 parts of an organic antioxidant, and 0.03-0.08 parts of nano-titanium dioxide are mixed at room temperature, and then 1-2 parts of hydrotalcite powder are added for grinding, and centrifuged by a centrifuge, and washed with anhydrous ethanol to obtain a modifier; S2. Preparation of modified adhesive: The modifier was added to 12-18 parts of elastic polyurethane adhesive and stirred evenly, and 0.05-0.1 parts of acetone was added to reduce the viscosity of the reaction system to obtain a modified adhesive; S3. Preparation of board: 80-85 parts of cork particles and the modified adhesive obtained in step S2 are mixed evenly in a glue mixer, and then added into a mold, and pressed at room temperature for 24-48 hours. The pressure is controlled at 0.1-0.2MPa, and the pressure is maintained and heated to 120-140℃ for hot pressing for 5-10 minutes to obtain a highly light-resistant and color-changing cork-based board.

2. The method for preparing a highly light-resistant and color-changing cork-based board material according to claim 1, characterized in that: The preparation of the multi-site polymer comprises the following steps: S11. The polyethyleneimine having a molecular weight of 1000-10000 is dissolved in water to prepare a polyethyleneimine aqueous solution having a mass fraction of 50-60%; S12. Add 10-15% of the mass of polybasic organic acid in the polyethyleneimine aqueous solution, and stir at 40-60° C. for 8-10 minutes to obtain a multi-site polymer.

3. The method for preparing a highly light-resistant and color-changing cork-based board material according to claim 2, characterized in that: The polybasic organic acid is one or more of trihydroxymethylpropane acid, tricarboxymethane acid and 3-carboxy-3-hydroxyglutaric acid.

4. The method for preparing a highly light-resistant and color-changing cork-based board material according to claim 1, characterized in that: In steps S2 and S3, the stirring speed is 300-500 r / min and the time is 10-15 min.

5. The method for preparing a highly light-resistant and color-changing cork-based board material according to claim 1, characterized in that: The elastic polyurethane adhesive is a two-component polyurethane adhesive consisting of component A and component B, wherein component A is a main agent, which is a polyurethane prepolymer containing terminal isocyanate groups and accounts for 65-70% of the mass fraction of the elastic polyurethane adhesive, and component B is a curing agent, which is a polyester polyol and accounts for 30-35% of the mass fraction of the elastic polyurethane adhesive.

6. The method for preparing a highly light-resistant and color-changing cork-based board material according to claim 1, characterized in that: The organic antioxidant is a hindered phenol antioxidant.

7. The method for preparing a highly light-resistant and color-changing cork-based board material according to claim 1, characterized in that: The average particle size of the nano titanium dioxide is 20-100 nm.

8. The method for preparing a highly light-resistant and color-changing cork-based board material according to claim 1, characterized in that: The preparation of the hydrotalcite comprises the following steps: S21. 1-2 parts by mass fraction of 60-70% aluminum nitrate aqueous solution, 2-4 parts by mass fraction of 60-70% magnesium nitrate aqueous solution, 1-2 parts by mass fraction of 60-70% sodium hydroxide aqueous solution, 3-7 parts by mass fraction of 60-70% sodium carbonate aqueous solution are slowly added dropwise together to obtain a slurry; S22. The obtained slurry was immediately transferred to an autoclave, aged at 90-100°C, centrifuged, washed several times with anhydrous ethanol, dried at 80-100°C, and crushed through an 80-mesh sieve to obtain hydrotalcite.

9. The method for preparing a highly light-resistant and color-changing cork-based board material according to claim 1, characterized in that: The cork particles have a particle size of 10-100 meshes.

10. The method for preparing a highly light-resistant and color-changing cork-based board material according to claim 1, characterized in that: In step S1, the grinding process is carried out in a planetary ball mill at a rotation speed of 800-1000 r / min for 1-2 h.

Citation Information

Patent Citations

  • Method of manufacturing natural cork film

    CN107953625A

  • A hydrophobic film for the surface of cork composite materials and its preparation method

    CN108587383B

  • ABS / vinyl cyanide-styrene resin composite material with function of generating negative ion, far-infrared ray or antimicrobial mildew resistant function

    CN101402777A

  • Graphene oxide grafted styrene-acrylonitrile copolymer compatibilizer modified bamboo-plastic cabinet board and preparation method thereof

    CN106147268A

  • PU (Polyurethane) refrigerator door seal production technology

    CN108864507A